Exploring the role of EBV ZEBRA antibody levels in papillary thyroid cancer risk and drug resistance - Jiaqin Deng; Yeqian Lai; Ming Yu; Yihua Gu; Lihong Qiu; Yuedong Wang (Discover Oncology)
Abstract Papillary thyroid carcinoma (PTC), the most prevalent thyroid malignancy worldwide, exhibits an increasing incidence globally despite its generally favorable prognosis. Although its etiology remains partially elucidated, recent investigations have implicated specific pathogens—notably Epstein-Barr virus (EBV)—in PTC pathogenesis. To rigorously evaluate the causal relationship between EBV ZEBRA antibody levels and PTC risk, we conducted a two-sample bidirectional Mendelian randomization (MR) analysis leveraging large-scale genome-wide association study (GWAS) data. For instrumental variable selection, we identified single nucleotide polymorphisms (SNPs) strongly associated with EBV ZEBRA antibody levels (exposure traits) using a discovery GWAS of 8191 White British individuals. The outcome analysis was performed against a Finnish cohort comprising 1472 PTC cases and 314,193 controls. Our primary analysis via inverse variance-weighting (IVW) revealed a significant positive association between genetically predicted higher EBV ZEBRA antibody levels and PTC risk (p = 0.0003; odds ratio [OR] = 1.19). Notably, the intercept term analysis showed no evidence of systematic level effect bias (p = 0.46). Sensitivity analyses using the weighted median method corroborated the main findings (p = 0.01; OR = 1.21), suggesting robustness against potential confounding factors. However, inherent limitations such as residual pleiotropy, genetic linkage disequilibrium, and population-specific allele frequencies necessitate cautious interpretation. These results collectively indicate that EBV ZEBRA antibody elevation may represent a biological marker for PTC susceptibility, offering novel mechanistic insights and potential targets for early detection and preventive strategies. Further translational studies are warranted to delineate the precise molecular pathways underlying this association.